CONVEYING ASMAUL HUSNA'S KNOWLEDGE VIA MOBILE APP FOR UNDERGRADS: HYBRIDIZING SIGNALING PRINCIPLE AND NIELSEN'S DESIGN GUIDELINES - Arifah Fasha Rosmani; Ariffin Abdul Mutalib; Siti Mahfuzah Sarif, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
With the evolution of mobile innovation, teaching asmaul husna to be engaging and exciting is possible. Therefore, this study aims to plan and develop a mobile app to effectively and competently prepare undergraduate students to learn asmaul husna. Signaling principles are chosen for this mobile application, as it is a very persuasive idea in digital learning in the same manner as Nielsen's design guidelines in the field of interaction design. (i) Asmaul Husna; (ii) Huraian Makna; (iii) Solusi Kehidupan and (iv) Kuiz Kefahaman, four separate parts of AHMA-SP (Asmaul Husna Mobile Application). This research presents an elective way to encourage students to learn asmaul husna and enhance their ability to memorize the definition of asmaul husna and their everyday life applications. It is evident from the test results provided on the level of knowledge through pre-test and post-test that there is a substantial improvement in this aspect. It is also proof that students have been able to understand the meaning and recall the names of Allah by implementing and incorporating the Signaling Principle and Nielsen's Design Guidelines.